Development of plasma and ion beam technology for material engineering at NCBJ - Nowakowska-Langier, K. (Вопросы атомной науки и техники, 2019)
The Plasma/Ion Beam Technology Division is one of several laboratories forming the Material Physics Department at the NCBJ in Świerk, Poland. Scientific activity of the Division concerns different aspects of research related to material engineering, surface engineering, functional properties characterization, as well as synthesis and modification of different materials.Plasma surface engineering methods like cathodic arc UHV deposition and pulsed magnetron sputtering methods as well as ion beam implantation methods are intensively exploited and developed in our laboratory. Відділення плазмових та іонно-пучкових технологій - одна з лабораторій відділу фізики матеріалів НЦЯД у Свєрці, Польща. Наукова діяльність відділення пов’язана з різними аспектами досліджень у галузі матеріалознавства, технології поверхні, визначення характеристик функціональних властивостей, а також синтезу й модифікації різних матеріалів. У лабораторії активно використовуються та розробляються методи плазмової обробки поверхні, такі як катодно-дугове осадження за надвисокого вакууму (UHV deposition), та методи імпульсного магнетронного розпилення, а також методи іонної імплантації. Отделение плазменных и ионно-пучковых технологий - одна из лабораторий отдела физики материалов НЦЯИ в Сверке, Польша. Научная деятельность отделения связана с различными аспектами исследований в области материаловедения, технологии поверхности, определения характеристик функциональных свойств, а также синтеза и модификации различных материалов. В лаборатории активно используются и разрабатываются методы плазменной обработки поверхности, такие как электронно-дуговое осаждение при сверхвысоком вакууме (UHV deposition), методы импульсного магнетронного распыления, а также методы ионной имплантации.